Evaluation of rejected wet carcass syndrome lamb meat for human or animal consumption - Hatting, Melissa (University of the Free State, 2023)
Wet carcass syndrome (WCS) is a condition found among sheep and is characterised by a ‘wet’ appearance of the subsurface meat at slaughtering. These carcasses are considered unfit for further use, resulting in financial loss to farmers and the industry as a whole. No preventions or cause have been determined for this syndrome, although WCS seems to be associated with winter/drought conditions. The current study compared twenty WCS carcasses to twenty unaffected normal carcasses to determine the quality and safety of the affected meat. Parameters tested included fat thickness, water holding capacity, colour, proximate analysis, fatty acid composition, water activity, pH and microbial load. A shelf-life study was performed on two products, i.e., lamb chops for human consumption and pet mince for the pet food industry. From morpho-physical examinations, WCS carcasses had measurements with significantly higher cold mass, external length, shoulder and buttock circumference than the normal carcasses. No significant differences were, however, found in the fatness and conformation code, showing that WCS-affected carcasses were physically larger, but retained the same level of fat around the outside of the carcass. Measurements taken between the 12ᵗʰ and 13ᵗʰ rib, showed normal carcasses had significantly higher fat thickness (45 mm and 110 mm), while WCS carcasses had significantly higher eye muscle width, depth, area and perimeter. The pH, temperature, water activity and water holding capacity had no significant differences. Proximate analysis included dry matter, moisture, protein, fat, organic matter and ash. All of these parameters showed higher levels in the normal vs WCS carcasses, except for moisture content which was higher in WCS vs normal carcasses. Nine of the fatty acids showed significant differences, where all but one, arachidic acid, had higher levels in the WCS, than in normal carcasses. From surface swabs, there were no differences in the number of microbes recovered from the surface of the WCS carcasses versus normal carcasses. Two products were formulated, lamb chops for human consumption and pet mince for the pet food industry. A shelf-life study (microbial load, colour and pH) determined the quality over a period of six days for lamb chops and 10 days for pet mince. The microbial load and pH on both products showed no significant differences between the WCS and normal carcasses, suggesting that WCS meat had the same microbial quality and was just as safe as that from a normal carcass. The colour analysis of the lamb chops showed no differences in the lightness nor the redness, although there was a difference in the blue/yellow colour on day 0, implying a greenish tint involved with WCS. This phenomenon, however, was only seen on day 0 and not throughout the 6-day experimental period. The study confirmed the safety of WCS meat for both human and animal consumption, although the wet surface appearance, soft texture and loose subcutaneous fat, is expected to still deter consumers from purchasing such meat. Processing of WCS meat into products like pet mince, will support new commercial ventures and lessen the financial impact of the condition on the livestock industry.
Dissertation (M.Sc.(Food Science))--University of the Free State, 2023
Keywords: Wet carcass syndrome; Sheep; Quality of meat; Human consumption; Pet consumption; Meat industry and trade; Mutton industry